H trapping and mobility in nanostructured tungsten grain boundaries: a combined experimental and theoretical approach. (8th September 2015) - González, C.; Panizo-Laiz, M.; Gordillo, N.; Guerrero, C.L.; Tejado, E.; Munnik, F.; Piaggi, P.; Bringa, E.; Iglesias, R.; Perlado, J.M.; González-Arrabal, R.
Abstract: The trapping and mobility of hydrogen in nanostructured tungsten grain boundaries (GBs) have been studied by combining experimental and density functional theory (DFT) data. Experimental results show that nanostructured W coatings with a columnar grain structure and a large number of (1 1 0)/(2 1 1) interfaces retain more H than coarsed grained W samples. To investigate the possible influence of GBs on H retention, a complete energetic analysis of a non-coherent W(1 1 0)/W(1 1 2) interface has been performed employing DFT. Our results show that this kind of non-coherent interface largely attracts point defects (both a H atom and a metallic monovacancy separately) and that the presence of these interfaces contributes to a decrease in the migration energy of the H atoms with respect to the bulk value. When both the W monovacancy and H atom are introduced together into the system, the HV complex becomes the most stable configuration and one of the mechanisms explaining the H retention in the radiation damaged GB observed experimentally.